Fortran Refactorings for Legacy Systems - Méndez, Mariano (2011)
This thesis is based on a certain type of legacy software that came from scientific research. Scientists have become one of the most important legacy code producers for many reasons. One of these is long-lived field (about 50 years old) they have been working in. Another reason is the amount of code produced through years and the lack of a well-defined software development process. Even though refactoring concept was born within the pale of object oriented programming we think that this concept is a paramount tool to be applied on Fortran source code. Since it has been successfully used in C language, our objective was to build a reference catalog which will serve as a guide to Fortran programmers. In thesis we discussed and proposed a detailed catalog of Fortran source transformation.